(untitled) (Papeles, 2018)
Youth unemployment and university dropout are the phenomena that represent a challenge to Colombian society, which call the national government’s attention when developing policies to provide a stable outlook of the opportunities for future generations. The present research was carried out by making a study among college students of the Universidad Nacional de Colombia, Bogotá Campus, in order to figure out and understand the relationship between these two phenomena.